2021
DOI: 10.1038/s41598-021-98415-9
|View full text |Cite|
|
Sign up to set email alerts
|

Moringa oleifera seeds-removed ripened pods as alternative for papersheet production: antimicrobial activity and their phytoconstituents profile using HPLC

Abstract: In the present study, and for the waste valorization, Moringa oleifera seeds-removed ripened pods (SRRP) were used for papersheet production and for the extraction of bioactive compounds. Fibers were characterized by SEM–EDX patterns, while the phytoconstituents in ethanol extract was analyzed by HPLC. The inhibition percentage of fungal mycelial growth (IFMG) of the treated Melia azedarach wood with M. oleifera SRRP extract at the concentrations of 10,000, 20,000, and 30,000 µg/mL against the growth of Rhizoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 93 publications
1
4
0
Order By: Relevance
“…1). Our results corroborate the findings of Salem et al , 59 who identified various polyphenols, like vanillic acid (5053.49 mg/100 g), benzoic acid (262.98 mg/100 g), etc. , as the main components of mature moringa pods from an HPLC chromatogram.…”
Section: Resultssupporting
confidence: 92%
“…1). Our results corroborate the findings of Salem et al , 59 who identified various polyphenols, like vanillic acid (5053.49 mg/100 g), benzoic acid (262.98 mg/100 g), etc. , as the main components of mature moringa pods from an HPLC chromatogram.…”
Section: Resultssupporting
confidence: 92%
“…Energy-dispersive X-ray spectroscopy analysis was performed to measure the changes in the elemental chemical composition of zucchini leaves (nine leaves for each treatment) due to different treatments with treated with 500 mg/L K 2 SiO 3 and control treatment. Energy-dispersive spectrometry (EDX), JFC-1100E ion sputtering device (model JEOL/MP, JSMIT200 Series, Tokyo, Japan) with acceleration voltage of 20.00 kV to show the elemental compotation at three point was used (Salem et al, 2021a ).…”
Section: Methodsmentioning
confidence: 99%
“…Elemental analysis of strawberry fruits was performed by scanning electron microscopy (SEM), attached with energy dispersive spectrometry (EDX), and a JFC-1100E ion sputtering device (model JEOL/MP, JSMIT200 Series, Tokyo, Japan) with an acceleration voltage of 20.00 kV (SEM-EDX) [55] to measure the changes in the elemental chemical composition of strawberry fruits due to different treatments.…”
Section: Elemental Analysis Of Strawberry Fruit Edx Analysismentioning
confidence: 99%